A Low Phase-Noise SiGe Colpitts VCO with Wide Tuning Range for UWB Applications - Eßwein, Alexander; Dehm-Andone, Gunther; Weigel, Robert; Aleksieieva, Anna; Vossiek, Martin (2010 European Wireless Technology Conference (EuWIT), 2010)
An integrated differential common collector Colpitts VCO with a wide tuning range is presented in this paper. The circuit was designed and fabricated in the IHP Technologies SGB25V 250nm SiGe:C BiCMOS process. It provides a superior low phase noise performance of −115 dBc/Hz covering the frequency range of 6.7 to 8.7 GHz for UWB pulsed frequency modulated secondary radar application. An additional common collector output buffer was implemented as well. The circuit provides an overall output power of −10dBm single-ended with a power dissipation of 47mW including the on-chip buffer. This paper also shows the modifications and improvements done at the mmwave topology to reduce size and to improve the tuning range.
lhft_intern.bib::Esswein2010